Educação do campo, juventude rural e inserção produtiva: o caso da formação de jovens rurais para o fortalecimento da agricultura camponesa do semiárido cearense - Falcão Júnior, Francisco Carlos (2018)
The present study studies the pedagogical action carried out by the Course: Training of Rural Youth for the Strengthening of Peasant Agriculture in the Semi-arid Cearense, offered by UNILAB / 2013-2014. Watching three hundred young people from the territories of Crateús, Canindé and Itapipoca. After each pedagogical action, it is imperative to know if its objectives have been reached. In this direction, the problem that the research raises is the contribution of the UNILAB Course in the professional activity of the trainees related to the productive insertion towards the improvement of life. Reference framework: qualitative research of the descriptive-explanatory type, the strategy applied will be a case study, with research conceptions and historical materialism, I worked with primary and secondary data, the research unit was the Jatobá Community of the Umbelinos in the territory of Crateús, for the mobility, articulation and concentration of subjects involved in the process and available for interviews. The documentary and bibliographical survey served to contextualize and to base the study, among the recording instruments, I emphasize the use of field diary, camera and recorder, where I used as methodological instruments: semi-structured interviews, focus group interviews, informal conversations, participatory observation and home visits, observing cultural antagonisms, I tried to understand the real through social contradictions from the perspective of the subjects themselves. The organization and selection of the data were done through the content analysis method through the units of content and context, when the categories of analysis were affirmed: contribution of the Course, productive insertion and pedagogical practice. I counted on the contributions of Freire (2011, 2014), Brandão (2006) and Ribeiro (2010) who dialogued and problematized the questions and concerns raised, helping in the elaboration and processes studied within the conceptual categories: rural education, rural youth and productive insertion.